EGFR/PI3K/Akt/mTOR pathway in head and neck squamous cell carcinoma patients with different HPV status - Janecka-Widła, Anna; Majchrzyk, Kaja; Mucha-Małecka, Anna; Biesaga, Beata (Polish Journal of Pathology, 2021)
The aim of the study was to compare prognostic potential of PIK3CA mutations and expression of proteins involved in or regulate EGFR/PI3K/Akt/mTOR signaling in HPV16 positive and HPV negative head and neck squamous cell carcinoma (HNSCC) patients. The expression of proteins (EGFR, Akt, pAkt(Ser473), pAkt(Thr308), mTOR, PTEN, pPTEN, APOBEC3B) were assessed immunohistochemically and PIK3CA mutations (p.E542K, p.E545K, p.H1047R) by qPCR. Significantly more HPV16 positive tumors (89.29%) with low EGFR expression were found as compared to HPV negative ones (58.82%). PIK3CA mutations were detected in 7.14% of HPV16 positive and 2.5% of HPV negative cancers. In HPV16 positive patients survival analysis has shown that positive prognostic potential for disease free survival (DFS) had low expression of APOBEC3B. In HPV negative patients prognostic significance for DFS had APOBEC3B, Akt and pAkt(Thr308) levels, and for overall survival (OS) – pAkt(Thr308) only. Independent favorable prognostic factors in the whole group of patients were: low T stage, low pAkt(Thr308) expression, active HPV16 infection (for OS and DFS) and female gender (for OS). Obtained results suggest the existence of significant differences in expression and prognostic potential of proteins involved in EGFR/PI3K/Akt/mTOR signaling between HPV16 positive and HPV negative HNSCC patients.